Javanese As Local Language Identity And Preservation In Digital Era - Dini Setiya; Swita Amallia Hapsari; Astini Kumalasari (Jurnal Ilmu Komunikasi, 2019)
Nowadays, in the development technology era, the local language waspredicted slowly dying, especially Javanese. The Internet has changed the society habit tospeak in English more often than local languages. Moreover, the current state describesthat Javanese language is considered as outdated so everyone never use the locallanguage in online communication. In the contrary, the digital brings fresh air for thelocal language to be known by the internet. A lot of content creators in Indonesia makevideos on YouTube using Javanese. Many of them succed deliver the content and showedthe identity of local language as well. Furthermore, the local language become theprimary content for content creators such as Dave Jepcott from Australian which popularand famous known as Londo Kampung. The method of this study is using a qualitativewith descriptive research. To obtain the primary data, the researchers using observationand interview technique. The result of this study showed that there are five elements thatinvolved and encourage people to find the identity and preservation for local languageswhich are the multiplicity of interpretation, value, attitude, meaning and knowledge form.Many people is considered to use Javanese language not only to preserve the locallanguage but also to present the unique value as a content that distributed to video onYouTube. Digital as the biggest challenge for culture evidently provide and give anopportunity to present the Javanese as local language for the identity.